2014
DOI: 10.3109/10717544.2014.907373
|View full text |Cite
|
Sign up to set email alerts
|

Lactobionic acid coupled liposomes: an innovative strategy for targeting hepatocellular carcinoma

Abstract: Introduction: Liver cancer or hepatocellular carcinoma (HCC) is a major cause of death worldwide. Targeted delivery of drug to the carcinoma cell can be achieved by conjugation of ligand on the carrier system. Methods and materials: In this study, oxaliplatin-loaded hepatoma-targeted liposome were designed and prepared using galactosylated distearoylphosphatidylethanolamine. The liposomes were prepared by cast film method and coupled with lactobionic acid (LA-LP) using 1-ethyl-3-(3-dimethylaminopropyl) carbodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…As a result, the distribution and efficiency of drug encapsulated by longcirculating immunoliposome are improved. Moreover, the therapy effect also has been improved due to its specifically discernment function for target tissues (Zalipsky, 1995, Mercadal et al, 1999, Torchilin et al, 2001, Susumu et al, 2007, Bansal et al, 2016, Yuan et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the distribution and efficiency of drug encapsulated by longcirculating immunoliposome are improved. Moreover, the therapy effect also has been improved due to its specifically discernment function for target tissues (Zalipsky, 1995, Mercadal et al, 1999, Torchilin et al, 2001, Susumu et al, 2007, Bansal et al, 2016, Yuan et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The uptake and organ distribution of the LA-LIP revealed that loaded drug prominently accumulated in the tumor. The results showed that liposome were a successful carrier for HCC targeting [15]. In conclusion, liposome is a promising carrier for targeted drug delivery in treating cancers.…”
mentioning
confidence: 76%
“…It was reported that the acute or chronic conditions of hepatic failure is fatal to our lives [16]. We knew that liposomes could be utilized for effective targeting delivery by receptor-mediated endocytosis [15]. Higuchi et al [17] showed that Kupffer cell-selective oligonucleotide could be carried through novel Fucose modified liposomes (Fuc-LIP) due to the recognition of fucose receptors on Kupffer cells.…”
mentioning
confidence: 99%
“…Additionally, galactose functionality has also been introduced into nanocarriers via lactobionic acid modification of nanocarrier‐forming amphiphiles . Chen et al .…”
Section: Targeted Bio‐functionalities Of Saccharide‐based Nanocarriersmentioning
confidence: 99%